Analyzing Writing of Producing Ideas and Using Mechanics through Showing Short Videos - Kartin Lihawa (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
This study addresses the challenges students face in writing, particularly in balancing writing theories with idea generation. It focuses on enhancing students' ability to produce clear and logical scientific writing by improving their mechanics application. Despite challenges faced by students in the English Department of FSB UNG, such as difficulty in writing long paragraphs and applying mechanics, the study aims to overcome these obstacles. The research, conducted through eight sessions of "Writing for Professional Context," utilizes short videos to facilitate idea generation and improve writing mechanics. The objectives include describing students' approaches to idea generation and mechanics application, minimizing deficiencies in these areas, and exploring improvements after intervention. The method involves descriptive qualitative analysis, incorporating tests on mechanics application and essay writing, with results scored using Anderson's criterion reference. Out of 19 students assessed, 4 demonstrated proficiency in the A category, 9 in the B category, and 6 in the C category. Ultimately, the research aims to publish an article in an international journal and secure intellectual property rights (HKI).